2019
DOI: 10.1002/jnm.2641
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fin width and gate structure on the performance of AlGaN/GaN fin‐shaped HEMTs

Abstract: In this paper, a systematic theoretical study on the fin-shaped AlGaN/GaN HEMTs with trigate structure and dual-gate structure is performed by TCAD simulation. The influence of different gate structures and fin width on the DC performance of the fin-shaped AlGaN/GaN high electron mobility transistors (HEMTs) are mainly studied and compared. A simplified physical analysis of the influence of fin width and gate structure on the threshold voltage is made. How to cite this article: Zhang M, Ma X, Mi M, et al. Infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Moreover, because of the lack of control from the top gate in the dual-gate structure, as W fin increased continuously, the threshold voltage of the DGN-devices decreased continuously without restriction. When further decreasing W fin to less than 100 nm, the V th of the TGN-devices and DGN-devices could be approximated [ 29 ], and the normally off TGN-devices and DGN devices could be realized. As shown in Figure 3 b, the gradients of the G m,peak –W fin curves for the tri-gate structure and dual-gate structure were similar, indicating the similar electrostatic charge control effect from the sidewall gates.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, because of the lack of control from the top gate in the dual-gate structure, as W fin increased continuously, the threshold voltage of the DGN-devices decreased continuously without restriction. When further decreasing W fin to less than 100 nm, the V th of the TGN-devices and DGN-devices could be approximated [ 29 ], and the normally off TGN-devices and DGN devices could be realized. As shown in Figure 3 b, the gradients of the G m,peak –W fin curves for the tri-gate structure and dual-gate structure were similar, indicating the similar electrostatic charge control effect from the sidewall gates.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Y. He et al and M. Zhang et al have reported fin‐shaped AlGaN/GaN‐based non‐planner HEMT (FinHEMT) structures and modeled threshold voltage by considering fin width (WFin$$ {W}_{\mathrm{Fin}} $$) into consideration along with fin height (HFin$$ {H}_{\mathrm{Fin}} $$) as a fitting parameter 12,13 . Similarly, Ren et al reported a compact model for electrical parameters like threshold voltage and drain characteristics of AlGaN/GaN metal insulator semiconductor (MIS) FinHEMT by incorporating 2‐Dimensional Poisson's equation in the GaN channel region while taking both strain reduction and metal‐GaN depletion effect due to WFin.$$ {W}_{\mathrm{Fin}}.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al reported an improved quasi‐physics zone division large‐signal model to account for electro‐thermal effects, which is valid for the ambient temperature range of 245 to 390 K. Physical parameters' effects, reliable parameter extraction, and dynamic thermal impedance extraction for the equivalent circuit models of GaN HEMTs are discussed by Mi et al, Chen et al, and Wang et al, respectively. The modeling of emerging devices is also presented by Chen et al for GaN‐on‐diamond HEMTs and Zhang et al for AlGaN/GaN fin‐shaped HEMTs, which may be interesting for next generation devices. Accurate modeling of transistors' noise performance is important for low‐noise applications.…”
mentioning
confidence: 99%